A meta‐regression of the impact of policy on the efficacy of individual placement and support. (19th December 2019) - Brinchmann, B.; Widding‐Havneraas, T.; Modini, M.; Rinaldi, M.; Moe, C. F.; McDaid, D.; Park, A‐L.; Killackey, E.; Harvey, S. B.; Mykletun, A.
Abstract : Objective: Individual placement and support (IPS) has shown consistently better outcomes on competitive employment for patients with severe mental illness than traditional vocational rehabilitation. The evidence for efficacy originates from few countries, and generalization to different countries has been questioned. This has delayed implementation of IPS and led to requests for country‐specific RCTs. This meta‐analysis examines if evidence for IPS efficacy can be generalized between rather different countries. Methods: A systematic search was conducted according to PRISMA guidelines to identify RCTs. Overall efficacy was established by meta‐analysis. The generalizability of IPS efficacy between countries was analysed by random‐effects meta‐regression, employing country‐ and date‐specific contextual data obtained from the OECD and the World Bank. Results: The systematic review identified 27 RCTs. Employment rates are more than doubled in IPS compared with standard vocational rehabilitation (RR 2.07 95% CI 1.82–2.35). The efficacy of IPS was marginally moderated by strong legal protection against dismissals. It was not moderated by regulation of temporary employment, generosity of disability benefits, type of integration policies, GDP, unemployment rate or employment rate for those with low education. Conclusions: The evidence for efficacy of IPS is very strong. The efficacy of IPS can be generalized between countries.